Cyst Fluid Carcinoembryonic Antigen Level Is not Predictive of Invasive Cancer in Patients with Intraductal Papillary Mucinous Neoplasm of the Pancreas - Kucera, Stephen; Centeno, Barbara A; Springett, Gregory; Malafa, Mokenge P; Chen, Yian Ann; Weber, Jill; Klapman, Jason (JOP. Journal of the Pancreas, 2012)
Context Cyst fluid CEA concentration >192ng/mL has proven accurate to differentiate mucinous from non-mucinous pancreatic cystic neoplasms. It is unclear whether the degree of cyst fluid CEA elevation is predictive of malignant behavior in IPMNs. Objectives To determine whether elevated cyst fluid CEA concentrations were predictive of invasive cancer. Design Cross sectional study. Setting Single National Cancer Institute comprehensive cancer care center experience. Patients Forty-seven patients underwent preoperative EUS-FNA with cyst fluid analysis and surgical resection of an IPMN over a 9 year period. Main outcome measurements Cyst fluid CEA concentrations among the four grades associated with IPMN (low grade dysplasia, moderate dysplasia, high grade dysplasia, and invasive cancer). Results The mean±standard deviation cyst fluid CEA concentration increased as the pathology progressed from low grade dysplasia (1,261±1,679 ng/mL) to moderate dysplasia (7,171±22,210 ng/mL) to high grade dysplasia (10,807±36,203 ng/mL). However, the mean CEA level decreased (462±631 ng/mL) once invasive cancer developed (P=0.869). The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of a cyst fluid CEA concentration greater than 200 ng/mL for the diagnosis of malignant IPMN (cases of high grade dysplasia and invasive IPMN) was 52.4%, 42.3%, 42.3%, 52.4% and 46.8%, respectively. Limitations Single center experience, small patient numbers, retrospective data collection. Conclusion The degree of cyst fluid CEA elevation is a poor predictor of malignant degeneration within IPMNs. Clinical management decisions regarding surgical resection should not be based upon degree of cyst fluid CEA elevation. Image: Box-plot comparing pre-operative CEA levels with surgical pathology.